2022
DOI: 10.1096/fj.202200152r
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing of the Mongolia sheep testis reveals a conserved and divergent transcriptome landscape of mammalian spermatogenesis

Abstract: Spermatogenesis is a highly coordinated and complex process, and is pivotal for transmitting genetic information between mammalian generations. In this study, we investigated the conservation, differences, and biological functions of homologous genes during spermatogenesis in Mongolia sheep, humans, cynomolgus monkey, and mice using single-cell RNA sequencing technology. We compared X chromosome meiotic inactivation events in Mongolia sheep, humans, cynomolgus monkey, and mice to uncover the concerted activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Another important type of re-analyses of human testicular scRNA-seq data is to do species or sex comparisons. For species comparison, so far, the spermatogenesis of mouse 165 , mouse lemur 165 , chicken 166 , cynomolgus macaque 167 , sheep 168 and the somatic development of pigs 169 has been fully compared with that of human. The similarities of these studies were that they reported both conserved (especially the conservatism of X chromosome inactivation) and species-specific features among different animals and human.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important type of re-analyses of human testicular scRNA-seq data is to do species or sex comparisons. For species comparison, so far, the spermatogenesis of mouse 165 , mouse lemur 165 , chicken 166 , cynomolgus macaque 167 , sheep 168 and the somatic development of pigs 169 has been fully compared with that of human. The similarities of these studies were that they reported both conserved (especially the conservatism of X chromosome inactivation) and species-specific features among different animals and human.…”
Section: Resultsmentioning
confidence: 99%
“…The similarities of these studies were that they reported both conserved (especially the conservatism of X chromosome inactivation) and species-specific features among different animals and human. A good example would be Tian et al's work, in which they compared the spermatogenesis of four different species (human, mouse, sheep and cynomolgus macaque) 168 . In that study, they found the spermatogenesis between sheep and human were partially conserved at the transcriptional level (e.g., similar regulators were expressed in the same stages of spermatogenesis in human and sheep) and further showed the high conservatism of X chromosome inactivation during meiosis among four species 168 , which was in line with Lau et al's report 167 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The candidate genes B4GALNT4 ( 33 ) involved in lactose synthesis, RCOR1 ( 34 ) related to milk yield and SH3D19 related to lactation process in sheep were also identified ( 35 ). In addition, our results contain a large number of candidate genes related to production traits, such as reproductive trait candidates: FSIP2 ( 17 ), CD226 ( 36 ), SLC44A5 ( 37 ), GPR83 ( 38 ), SUN5 ( 39 ), GPR173 ( 40 ), LHX8 ( 41 ), SIRT3 ( 42 ), FGF16 ( 43 ), POU3F4 ( 44 ), these genes affect reproductive traits by influencing days of estrus, luteal gland, participating in reproductive regulation, and hypothalamic-pituitary-gonadal axis regulation. For example, the candidate genes for wool traits: RALY ( 45 ), GLI2 ( 46 ), TXNRD3 ( 47 ), EIF2S2 ( 45 ), IRF2BP2 ( 48 ), etc.…”
Section: Discussionmentioning
confidence: 99%
“…In farm animals, testicular scRNA‐seq studies have been performed on sheep (Tian et al., 2022; Yang et al., 2021), goat (Ren et al., 2022), buffalo (Huang et al., 2022), and yak (Wang, Pei, et al., 2023). In pigs, male germ cells and somatic cells (3 types) were defined first on the mature testis of a Chinese local pig breed (Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%